2021
DOI: 10.3390/mi12091045
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Dynamic Characteristics Analysis and Experimental Research of Tri-Stable Piezoelectric Energy Harvester

Abstract: In order to explore the dynamic characteristics of the linear-arch beam tri-stable piezoelectric energy harvester (TPEH), a magnetic force model was established by the magnetic dipole method, and the linear-arch composite beam nonlinear restoring force model was obtained through experiments. Based on the Euler–Bernoulli beam theory, a system dynamic model is established, and the influence of the horizontal distance, vertical distance and excitation acceleration of magnets on the dynamic characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Kim and Seok [29] researched the bifurcation mechanism of a traditional TH. Zhang et al [30] incorporated structural nonlinearity into a TH and studied its dynamic response. Wang et al [31] developed a TH with the utilization of an elastic base, enhancing the ability to harvest energy during low-orbit vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Seok [29] researched the bifurcation mechanism of a traditional TH. Zhang et al [30] incorporated structural nonlinearity into a TH and studied its dynamic response. Wang et al [31] developed a TH with the utilization of an elastic base, enhancing the ability to harvest energy during low-orbit vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear designs using cantilever structure and magnetic interaction are good ways to extend the operational bandwidth because of their simple configurations and large oscillation amplitudes. Nonlinear piezoelectric energy harvesters that adopt cantilever structure and magnetic interaction consist of mono-stable piezoelectric energy harvesters (MPEHs) [30][31][32], bi-stable piezoelectric energy harvesters (BPEHs) [33][34][35][36][37][38], tri-stable piezoelectric energy harvesters (TPEHs) [39][40][41][42][43][44], quad-stable piezoelectric energy harvesters (QPEHs) [45][46][47][48][49], pentastable piezoelectric energy harvesters (PPEH) [50,51], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [42] studied the influence of potential well depth on the performance of a conventional TPEH. Zhang et al [43] introduced structural nonlinearity to a TPEH by an arched piezoelectric beam, and studied its time-domain dynamic characteristics. Sun et al [44] presented a dual-magnet TPEH and investigated its performance under the random excitation of 0-120 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue focuses on state-of-the-art vibration sensing and energy harvesting technologies. After being carefully reviewed, 11 articles have been accepted for publication in this Special Issue [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] that can be divided into three aspects: (i) new materials for vibration energy harvesting applications, (ii) design and fabrication of vibration energy harvesters (VEHs), and (iii) system-level integration and testing of VEHs.…”
mentioning
confidence: 99%
“…Furthermore, Zhang et al reported a tri-stable piezoelectric energy harvester based on a linear-arch composite beam. The experiment result shows that the system can be mono-stable, bi-stable, and tri-stable by adjusting the horizontal or vertical spacing of the magnets [ 11 ]. Xu et al utilized the vibration energy to drive a single-phase ultrasonic motor directly.…”
mentioning
confidence: 99%